2022
DOI: 10.22161/jhed.4.2.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interpersonal Conflict, Job Stress, and Work Life Balance on Employee Turnover Intention

Abstract: Staff providing services to clients is a common feature of the private sector. To remain competitive, the private sector must maintain high-quality and consistent services. The aim of this study to analyze the influence of interpersonal conflict, job stress, and work life balance on employee turnover intention. Quantitative research was applied to measure the current study. A random sampling method was used to gather data. The researchers distribute 120 questionnaires. 112 questionnaires were received but only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…Based on this it can be seen that the first hypothesis in this study is accepted. The results of this study are in line with the results of research conducted by Yu et al (2022), Ahmad (2022) and Kerdpitak & Jermsittiparsert (2020) which revealed that there is a significant positive effect between work life balance on turnover intention. Ramdhani, et al (2018) work life balance is the achievement of quality of life because individuals are able to manage the complexities of the world of work and their personal world.…”
Section: Effect Of Work Life Balance On Turnover Intentionsupporting
confidence: 91%
“…Based on this it can be seen that the first hypothesis in this study is accepted. The results of this study are in line with the results of research conducted by Yu et al (2022), Ahmad (2022) and Kerdpitak & Jermsittiparsert (2020) which revealed that there is a significant positive effect between work life balance on turnover intention. Ramdhani, et al (2018) work life balance is the achievement of quality of life because individuals are able to manage the complexities of the world of work and their personal world.…”
Section: Effect Of Work Life Balance On Turnover Intentionsupporting
confidence: 91%
“…Kelly et al (2020) connected WLB with job stress, burnout, and job satisfaction. Gribben and Semple (2021) connect WLB with job stress and burnout, while Ahmad (2022) explains the relationship of WLB to job stress, interpersonal conflict, and employee turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, great teachers aim to balance their personal and professional life, leading to better time management skills. However, there is a connection between stress, work-life tension, and employee turnover (Ahmad, 2022). Therefore, the more one learns how to manage job and family life, the more effective and productive they become.…”
Section: Introductionmentioning
confidence: 99%